Topical cidofovir for recalcitrant viral warts in two children. - Calista, D. (European Journal of Pediatric Dermatology, 2000)
Over the last few years, new encouraging pharmacological approaches for the treatment of viral diseases have been evaluated. Among these is cidofovir, an inhibitor of the viral DNA synthesis. We report two patients, the first affected by plane warts of the face and the second by giant plantar wart, who were resistant to conventional therapies but promptly responded to a cream containing 1% cidofovir. Cidofovir, which is a purine nucleotide analogue of cytosine, is a promising new drug acting against a wide number of DNA viruses. Approved by intravenous administration only for the treatment of cytomegalovirus retinitis in patients with AIDS, recently topical cidofovir was found effective for the treatment of viral cutaneous lesions induced by herpes, pox and papilloma virus families.